Pemanfaatan Media Sosial dalam Flipped Classroom untuk Pengembangan Model Pembelajaran Blended Learning di Sekolah Pedesaan - Priyono Tri Febrianto; Ade Cyntia Pritasari; Aditya Dyah Puspitasari; Sabri Sulaiman (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
In the digital era, the utilization of social media is very important. In the world of education, social media has been massively used since the COVID-19 pandemic, where learning is mainly done online. This study aims to examine the utilization of social media in a flipped classroom to develop blended learning in elementary schools in rural areas. This study uses a quantitative approach with a descriptive research type. The utilization of social media for learning media makes it easier for someone to understand certain learning materials because wherever and whenever we can access the learning media and can even be repeated. In addition, through social media, students and teachers can also share learning information easily. The utilization of social media for learning is very necessary even in the post-pandemic era because science and technology will continue to develop hand in hand. The utilization of social media is the right step in achieving an interactive and quality learning process. The existence of social media platforms makes it easier for students to explore information and knowledge, as well as play an active role, such as asking questions and digging deeper into what they don't know.